Application of mineral-carbon composite in solid-phase extraction of phthalates from water - Dariusz Wideł; Piotr M. Słomkiewicz; Sabina Dołęgowska (Desalination and Water Treatment)
This study investigates the effectiveness of the mineral-carbon composite (C-HK), synthesized from a sucrose precursor and modified with calcined halloysite through a carbonization process, as a sorbent for the solid-phase extraction (SPE) of phthalate acid esters (PAEs) from aqueous samples, with subsequent analysis performed using gas chromatography-mass spectrometry (GC-MS). The adsorptive properties of the studied mineral-carbon composite (C-HK) were characterized using nitrogen adsorption isotherms and scanning electron microscopy, revealing a specific surface area of 42.15 m² g⁻¹ and mesoporosity of 99 %. The application of the material in the SPE of six phthalate acid esters (DMP, DEP, DBP, BBP, DEHP, and DOP) resulted in recovery rates ranging from 78 % to 100 %. Additionally, the composite exhibited good reusability, maintaining recovery values as high as 94 % after repeated use without replacing the sorbent. The comparison of the mineral-carbon composite (C-HK) with commercially available sorbents, such as C-18 and Florisil, as well as other materials described in the literature, demonstrated that the C-HK composite achieved higher recovery rates (∼10 %) for PAEs, emphasizing its effectiveness and suitability for such applications.